2008
DOI: 10.1194/jlr.m700486-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of biotin-anandamide, a novel tool for the visualization of anandamide accumulation

Abstract: Anandamide (N-arachidonoylethanolamide; AEA) acts as an endogenous agonist of both cannabinoid and vanilloid receptors. During the last two decades, its metabolic pathways and biological activity have been investigated extensively and relatively well characterized. In contrast, at present, the effective nature and mechanism of AEA transport remain controversial and still unsolved issues. Here, we report the characterization of a biotinylated analog of AEA (b-AEA) that has the same lipophilicity of the parent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Our study focused upon FABP5 as it is widely expressed across multiple cell types and mammalian tissues (6,22,44) and its inhibition likely underlies the efficacy of transport inhibitors in many cells. For example, AEA uptake is reduced by transport inhibitors in neurons and HaCaT keratinocytes, which express FABP5 (15,22,(45)(46)(47). Although our study focused upon FABP5, it is noteworthy that FABP3 and FABP7 bind to NAEs with relatively similar affinities (Table 1), and a similar trend may exist for transport inhibitors.…”
Section: Discussionmentioning
confidence: 87%
“…Our study focused upon FABP5 as it is widely expressed across multiple cell types and mammalian tissues (6,22,44) and its inhibition likely underlies the efficacy of transport inhibitors in many cells. For example, AEA uptake is reduced by transport inhibitors in neurons and HaCaT keratinocytes, which express FABP5 (15,22,(45)(46)(47). Although our study focused upon FABP5, it is noteworthy that FABP3 and FABP7 bind to NAEs with relatively similar affinities (Table 1), and a similar trend may exist for transport inhibitors.…”
Section: Discussionmentioning
confidence: 87%
“…Finally, we took advantage of the glass support to develop a fl uorescence-based method for studying import and export of AEA by confocal microscopy, using a biotinylated analog of AEA (b-AEA). This substance provides a nonradioactive tool for visualizing the movement of this lipid in intact cells ( 28,39 ). The time-dependent accumulation assay showed that the uptake of b-AEA in both cell types occurred within minutes ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…This new approach was successfully applied also to the measurement of AEA export from cells. Additionally, we demonstrated that a biotinylated derivative of AEA (b-AEA) ( 28,39 ) can be used to visualize the in-and-out traffi c of this endocannabinoid by immunofl uorescence techniques, providing a nonradioactive, rapid, and easy-to-use alternative for the study of anandamide metabolism.…”
Section: Export Assay With [mentioning
confidence: 99%
“…The results presented thus far suggest that the transmembrane transport and subsequent intracellular delivery of AEA to FAAH is rapid. The hydrophobicity of AEA (estimated LogP value of 5.1 (41)) suggests that it is unlikely to diffuse efficiently from the plasma membrane to intracellular membranes containing FAAH unaided. Because AEA is taken up and hydrolyzed by all cells that natively express and those transfected with FAAH (23)(24)(25), it is likely that AEA may share an intracellular delivery system used by other endogenous lipophilic molecules.…”
Section: Aea Cellular Uptake Is Rapid and Independent Of Subcellular mentioning
confidence: 99%